Pretreatment HDL‐C and ApoA1 are predictive biomarkers of progression‐free survival in patients with EGFR mutated advanced non‐small cell lung cancer treated with TKI. Issue 8 (10th March 2022) - Ma, Juan; Bai, Ying; Liu, Mei; Jiao, Tong; Chen, Yang; Yuan, Bo; Liu, Boxuan; Zeng, Lizhong; Ming, Zongjuan; Li, Wei; Sun, Ruiying; Yang, Xia; et al.
Abstract: Background: We aimed to explore the correlation between blood lipids (high density lipoprotein cholesterol [HDL‐C] and apolipoprotein A1 [ApoA1]) and epidermal growth factor receptor (EGFR) T790M mutation, as well as its predictive role in clinical efficacy and progression‐free survial (PFS) in advanced non‐small cell lung cancer (NSCLC) patients treated with EGFR tyrosine kinase inhibitors (EGFR‐TKI). Methods: We retrospectively collected information of 153 patients with advanced NSCLC harboring exon EGFR mutation and receiving EGFR‐TKI. Results: The best cutoff value for HDL‐C and ApoA1 was determined to be 1.15 and 1.14 mmol/l. The overall response rate (ORR) was 67.7% in the high HDL‐C group and 46.6% in the low HDL‐C group, respectively. The ORR of the high ApoA1 group showed a significant increase than that of the low ApoA1 group (68.1% vs. 38.5%). The mean ApoA1 level of the EGFR T790M mutation‐positive group was significantly higher than that of the EGFR T790M mutation‐negative group (1.13 g/l vs. 1.01 g/l). Patients with high ApoA1 levels were related to the EGFR T790M mutation ( r = 0.324). (3) The median progression‐free survival (PFS) of the high HDL‐C group and low HDL‐C group were 13.00 months and 10.20 months. The median PFS of the high ApoA1 group and the low ApoA1 group were 12.10 and 10.00 months, respectively. Multivariate Cox stepwise regression model analysis demonstrated ECOG PS, pathological type and HDL‐C were confirmed as critical and independent predictors of PFS. Conclusions: Patients with EGFR T790M mutations often show higher ApoA1 levels. Peripheral serum HDL‐C and ApoA1 before treatment can be used as potential significant factors for predicting clinical efficacy and PFS in advanced NSCLC patients treated with EGFR‐TKI. Abstract : We retrospectively collected information of 153 patients with advanced non‐small cell lung cancer (NSCLC) harboring exon epidermal growth factor receptor ( EGFR ) mutation and receiving EGFR tyrosine kinase inhibitors (EGFR–TKI). The study demonstrated ApoA1 after drug resistance was lower than before treatment, and patients with EGFR T790M mutation often show higher apolipoprotein A1 (ApoA1) levels. High density lipoprotein cholesterol (HDL–C) and ApoA1 can be used as critical predictive biomarkers for clinical efficacy and PFS in NSCLC patients treated with EGFR–TKI.